A polymer composite material for warning light housing and preparation method thereof
By adding UV-resistant and high-temperature resistance additives to the warning lamp housing material, the physical crosslinking of polymers and graphene oxide and the chemical crosslinking of vinyl silicone resin and talc powder are solved, and the problem of insufficient UV-resistant and high-temperature resistance of polyethylene materials is significantly extended and its mechanical properties are improved.
Patent Information
- Application Number
- CN202410625067.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-05-20
AI Technical Summary
As a warning lamp housing material, polyethylene has poor UV resistance and high temperature resistance, resulting in a short service life in outdoor environments.
A polymer composite material is adopted, including 60-90 parts of polyethylene, 2-5 parts of anti-ultraviolet additives, 3-7 parts of high-temperature resistant additives, 1-4 parts of lubricant, 1-3 parts of plasticizers, and 2-4 parts of crosslinking agents. The physical crosslinking of 2-hydroxy-4-(methacryloyloxy)benzophenone in the anti-ultraviolet additives and graphene oxide, and the chemical crosslinking of vinyl silicone resin in the high-temperature resistant additives and talc powder, improve the UV resistance and high-temperature resistant properties of the material.
It significantly improves the UV resistance and high temperature resistance of polyethylene composite materials, extends the service life of the material, and enhances its mechanical properties.
Smart Images

Figure CN118480223B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, in particular to a polymer composite material for a warning light housing and a preparation method thereof. Background Art
[0002] Warning lights are devices used for reminders, indications or warnings. They are widely used in industries, transportation, medical treatment and public safety, and can improve production safety. Warning light shells are usually made of different materials, generally metal and plastic. Warning light shells made of metal are heavy and not insulated, with a low safety factor, high processing difficulty, high cost, and poor heat dissipation. In comparison, warning light shells made of plastic are lighter, less expensive, and have good insulation. Warning light shells made of plastic are generally made of polycarbonate, polypropylene, ABS, polyethylene, etc. Among them, polyethylene has good low temperature resistance, good corrosion resistance and wear resistance, excellent electrical insulation, high ductility and impact strength, good chemical stability, and can make the product durable and safe. The material is common and low in cost. Therefore, polyethylene is selected as the base material of the warning light shell. However, in order to ensure that the warning light shell can have a long service life in an outdoor working environment for a long time, the high temperature resistance and UV resistance of polyethylene need to be further improved.
[0003] The patent with publication number CN115490940B discloses an anti-fog, breathable, aging-resistant transparent polyethylene composite material, which includes polyethylene resin, anti-fog stabilizer, and the anti-fog stabilizer includes interface modifier, methylphenyl vinyl silicone rubber, nano calcium carbonate material, coupling agent, antioxidant and light stabilizer. By optimizing the formula of the anti-fog stabilizer, the anti-fog droplet agent will not migrate out, the breathable and anti-fog performance of polyethylene is improved, and the anti-fog effect is longer. At the same time, the polyethylene obtained has excellent aging resistance and can maintain good mechanical properties under the influence of environmental factors for a long time. However, the patent does not take into account the high temperature resistance of polyethylene as a warning light housing in outdoor environments, and there are still defects in practical applications. For this reason, the present invention provides a polymer composite material that can be directly used to make a warning light housing. Summary of the invention
[0004] The purpose of the present invention is to provide a polymer composite material for a warning light and a preparation method thereof, so as to solve the following technical problems:
[0005] (1) Solved the problem of poor UV resistance of polyethylene;
[0006] (2) The problem of poor high temperature resistance of polyethylene has been solved.
[0007] The purpose of the present invention can be achieved through the following technical solutions:
[0008] A polymer composite material for a warning light housing comprises the following raw materials in parts by weight: 60-90 parts of polyethylene, 2-5 parts of anti-ultraviolet additives, 3-7 parts of high temperature resistant additives, 1-4 parts of lubricants, 1-3 parts of plasticizers, and 2-4 parts of cross-linking agents.
[0009] Furthermore, the preparation method of the anti-ultraviolet additive comprises the following steps:
[0010] Step 1: Add 2-hydroxy-4-(methacryloyloxy)benzophenone to ethanol and mix well, then add initiator, heat to 80-90°C, stir for 1-2h, and obtain UV-resistant polymer;
[0011] Step 2: Add graphene oxide to N,N-dimethylformamide and mix, ultrasonically disperse for 10-15 minutes to form a uniform dispersion, then add glycerol and anti-ultraviolet polymer, stir at room temperature for 3-5 hours, separate, filter, wash, and dry to obtain an anti-ultraviolet additive.
[0012] By adopting the above technical scheme, 2-hydroxy-4-(methacryloyloxy)benzophenone can undergo self-polymerization reaction under the action of an initiator to form a polymer containing a benzophenone ultraviolet absorption functional group. The polymer is entangled and coated with graphene oxide through the physical cross-linking effect of glycerol to form a composite to obtain an anti-ultraviolet additive.
[0013] Furthermore, in step 1, the initiator is ammonium persulfate.
[0014] Furthermore, the preparation method of the high temperature resistant additive comprises the following steps:
[0015] Step A, adding talc powder to toluene, stirring evenly to form a suspension, adding 3-mercaptopropionic acid and a catalyst, heating to 90-100° C., stirring for 1-2 hours, filtering, and drying to obtain modified talc powder;
[0016] Step B: adding modified talc to tetrahydrofuran, stirring evenly, adding vinyl silicone resin and photoinitiator, reacting under ultraviolet light for 1-2 hours, filtering, and drying to obtain a high temperature resistant additive.
[0017] By adopting the above technical scheme, under the action of a catalyst, the active hydroxyl groups on the surface of talcum powder can undergo an esterification reaction with the carboxyl groups in 3-mercaptopropionic acid to obtain modified talcum powder. The mercapto groups in the structure of the modified talcum powder can undergo a mercapto-ene click reaction with the unsaturated olefins in the vinyl silicone resin under ultraviolet light irradiation and the action of a photoinitiator to obtain a high temperature resistant additive.
[0018] Furthermore, in step A, the catalyst is p-toluenesulfonic acid.
[0019] Furthermore, in step B, the photoinitiator is benzoin dimethyl ether.
[0020] Furthermore, in step B, the vinyl content of the vinyl silicone resin is 1.4%.
[0021] Furthermore, the lubricant is one or more of calcium stearate, magnesium stearate, and iron stearate; the plasticizer is tri-n-butyl citrate or dioctyl sebacate; and the cross-linking agent is one of diisopropyl peroxide, benzoyl peroxide, or di-tert-butyl peroxide.
[0022] A method for preparing a polymer composite material for a warning light housing comprises the following steps:
[0023] The first step is to add polyethylene, anti-ultraviolet additives, high temperature resistant additives, lubricants, plasticizers, and cross-linking agents into a mixer for mixing at a speed of 50-80 r / min for 15-30 min to obtain a mixed material;
[0024] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material through melt extrusion, cooling, and pelletizing.
[0025] Furthermore, in the second step, during the melt extrusion, the temperature is set to 160-220° C. and the twin-screw speed is set to 80-150 r / min.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention utilizes a polymer with ultraviolet absorption function to undergo physical cross-linking with graphene oxide to form a composite to prepare an anti-ultraviolet additive. The polymer can stretch out the graphene oxide sheets, thereby solving the problem of stacking and agglomeration between the graphene oxide sheets. The polymer can improve the compatibility of graphene oxide with polyethylene and is evenly dispersed in the polyethylene matrix to form a sheet-like barrier absorption layer. The polymer structure is combined with the abundant benzophenone ultraviolet absorption functional groups to achieve the effect of efficient and effective absorption of ultraviolet light, thereby enhancing the anti-ultraviolet ability of polyethylene, slowing down the aging of polyethylene, and extending the service life of the composite material.
[0028] (2) The vinyl silicone resin in the high temperature resistant additive prepared by the present invention contains unsaturated olefin groups that do not participate in the reaction, and can be cross-linked with the polyethylene molecular chain under the action of the cross-linking agent, so that the polyethylene molecular chain has a higher density, inhibits the thermal motion of the molecular chain, and improves the thermal stability of the composite material. At the same time, talcum powder is combined with the polyethylene matrix in the form of chemical bonds, which effectively improves the compatibility of talcum powder and polyethylene, thereby efficiently utilizing the advantages of talcum powder and enhancing the mechanical properties of the composite material.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 is a scanning electron microscope image of graphene oxide and an anti-ultraviolet additive in Example 1 of the present invention, wherein A is a scanning electron microscope image of graphene oxide, and B is a scanning electron microscope image of the anti-ultraviolet additive;
[0032] Figure 2 This is the infrared spectrum of the high temperature resistant additive in Example 1 of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Example 1
[0035] 1. Preparation of anti-ultraviolet additives
[0036] Step 1: Add 6 g of 2-hydroxy-4-(methacryloyloxy)benzophenone to ethanol and mix well, then add 0.2 g of ammonium persulfate, heat to 85° C., and stir for 1.5 h to obtain an anti-ultraviolet polymer;
[0037] Step 2: Add 1 g of graphene oxide to N,N-dimethylformamide, mix, and ultrasonically disperse for 15 minutes to form a uniform dispersion. Then add 0.2 g of glycerol and 5 g of anti-UV polymer, stir at room temperature for 4 hours, separate, filter, wash, and dry to obtain an anti-UV additive.
[0038] Scanning electron microscopy analysis of graphene oxide and anti-ultraviolet additives showed the following test results: Figure 1 , where A is the scanning electron microscope image of graphene oxide, and B is the scanning electron microscope image of the anti-ultraviolet additive. Figure 1 It can be seen that the surface of graphene oxide is very smooth, while the surface of the anti-UV additive has a rough coating layer, presenting a coating structure. This is because the anti-UV polymer is entangled and coated on the surface of graphene oxide to form a composite.
[0039] 2. Preparation of high temperature resistant additives
[0040] Step A, adding 2.8 g of talc to toluene, stirring evenly to form a suspension, adding 5.5 g of 3-mercaptopropionic acid and 0.2 g of p-toluenesulfonic acid, heating to 100° C., stirring for 1.5 h, filtering, and drying to obtain modified talc;
[0041] Step B: Add 2.4 g of modified talc to tetrahydrofuran, stir evenly, add 5 g of vinyl silicone resin with a vinyl content of 1.4% and 0.1 g of benzoin dimethyl ether, and place under ultraviolet light (light intensity 20 mW / cm 2 ) was irradiated and reacted at room temperature for 1.5 h, filtered, and dried to obtain a high temperature resistant additive.
[0042] The sample was prepared by potassium bromide tablet method, and infrared test of high temperature resistant additives was carried out by Fourier infrared spectrometer, such as Figure 2 As shown, the spectral wavenumber test range is 4000cm -1 -500cm -1 , analysis shows that in the infrared spectrum of modified talc, 2540cm -1 The absorption peak of thiol appeared at 1730cm -1 The absorption peak of ester group appeared at 1041cm -1 The absorption peak of silicon-oxygen bond appears at 2540cm in the infrared spectrum of high temperature resistant additive. -1 The thiol absorption peak at 1196 cm -1 The absorption peak of thioether bond appeared at , indicating that the high temperature resistant additive was successfully prepared.
[0043] 3. Preparation of composite materials
[0044] The first step is to add 60g polyethylene, 2g anti-ultraviolet additive, 3g high temperature resistant additive, 1g calcium stearate, 1g tri-n-butyl citrate, and 2g diisopropylbenzene peroxide into a mixer and mix them at a speed of 50r / min for 30min to obtain a mixed material;
[0045] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 160° C. and the twin-screw speed is 140 r / min.
[0046] Example 2
[0047] Preparation of composite materials
[0048] The first step is to add 70g polyethylene, 3g anti-ultraviolet additive, 4g high temperature resistant additive, 2g calcium stearate, 2g tri-n-butyl citrate, and 3g diisopropylbenzene peroxide into a mixer and mix them at a speed of 60r / min for 25min to obtain a mixed material;
[0049] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 180° C. and the twin-screw speed is 120 r / min.
[0050] The preparation method of the anti-ultraviolet additive and the preparation method of the high temperature resistant additive are the same as those in Example 1.
[0051] Example 3
[0052] Preparation of composite materials
[0053] The first step is to add 80g polyethylene, 4g anti-ultraviolet additive, 5g high temperature resistant additive, 3g calcium stearate, 3g tri-n-butyl citrate, and 4g diisopropylbenzene peroxide into a mixer and mix them at a speed of 70r / min for 20min to obtain a mixed material;
[0054] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 200° C. and the twin-screw speed is 100 r / min.
[0055] The preparation method of the anti-ultraviolet additive and the preparation method of the high temperature resistant additive are the same as those in Example 1.
[0056] Example 4
[0057] Preparation of composite materials
[0058] The first step is to add 90g polyethylene, 5g anti-ultraviolet additive, 6g high temperature resistant additive, 4g calcium stearate, 3g tri-n-butyl citrate, and 4g diisopropylbenzene peroxide into a mixer and mix them at a speed of 80r / min for 15min to obtain a mixed material;
[0059] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 220° C. and the twin-screw speed is 80 r / min.
[0060] The preparation method of the anti-ultraviolet additive and the preparation method of the high temperature resistant additive are the same as those in Example 1.
[0061] Comparative Example 1
[0062] Preparation of composite materials
[0063] The first step is to add 70g polyethylene, 4g high temperature resistant additive, 2g calcium stearate, 2g tri-n-butyl citrate, and 3g diisopropylbenzene peroxide into a mixer and mix them at a speed of 60r / min for 25min to obtain a mixed material;
[0064] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 180° C. and the twin-screw speed is 120 r / min.
[0065] The preparation method of the high temperature resistant additive is the same as that in Example 1.
[0066] Comparative Example 2
[0067] Preparation of composite materials
[0068] The first step is to add 70g polyethylene, 3g anti-ultraviolet additive, 2g calcium stearate, 2g tri-n-butyl citrate, and 3g diisopropylbenzene peroxide into a mixer and mix them at a speed of 60r / min for 25min to obtain a mixed material;
[0069] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 180° C. and the twin-screw speed is 120 r / min.
[0070] The preparation method of the anti-ultraviolet additive is the same as that in Example 1.
[0071] Comparative Example 3
[0072] Preparation of composite materials
[0073] The first step is to add 70g polyethylene, 3g anti-ultraviolet additive, 4g talcum powder, 2g calcium stearate, 2g tri-n-butyl citrate, and 3g diisopropylbenzene peroxide into a mixer and mix them at a speed of 60r / min for 25min to obtain a mixed material;
[0074] The second step is to add the mixed material into a twin-screw extruder, and obtain a polyethylene composite material by melt extrusion, cooling, and pelletizing, wherein the twin-screw extrusion temperature is 180° C. and the twin-screw speed is 120 r / min.
[0075] The preparation method of the anti-ultraviolet additive is the same as that in Example 1.
[0076] Performance Testing
[0077] Performance test of polymer composite materials for warning light housing prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 3:
[0078] The composite materials in the embodiments and comparative examples were prepared into plastic specimens of 100*100*2 mm, and the tensile strength of the composite materials was tested according to GB / T1040.1-2018; the impact strength of the composite materials was tested according to GB / T 1043.1-2008; after aging for 240 h according to the method of GB / T 16422.2-2022, the tensile strength of the composite materials was tested to detect the UV resistance of the composite materials; the thermal deformation temperature of the composite materials was tested according to GB / T 1634.2-2019.
[0079]
[0080] It can be seen from the above table that the polymer composite materials for warning light housings prepared in Examples 1 to 4 have good mechanical properties, high temperature resistance and UV resistance, among which the test result of Example 2 is the best. Comparative Example 1 does not add anti-UV additives, and the test results show that the tensile strength after aging is significantly decreased. This is because the polyethylene composite material does not contain substances with UV absorption, and it is impossible to utilize graphene oxide and polymers with UV absorption to entangle with each other to form a barrier absorption layer to absorb UV light, thereby accelerating the aging rate. Comparative Example 2 does not add high temperature resistant additives, and the test results show that the heat deformation temperature is low, because it is impossible to utilize high temperature resistant additives to cross-link with polyethylene to inhibit molecular thermal motion and achieve the purpose of improving the thermal stability of the composite material; Comparative Example 3 adds talcum powder, and the test results show that talcum powder can enhance the mechanical properties of the composite material, and at the same time, it can also enhance the high temperature resistance of the composite material to a certain extent.
[0081] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A polymer composite material for a warning light housing, characterized in that: The invention comprises the following raw materials in parts by weight: 60-90 parts of polyethylene, 2-5 parts of anti-ultraviolet additives, 3-7 parts of high temperature resistant additives, 1-4 parts of lubricants, 1-3 parts of plasticizers, and 2-4 parts of cross-linking agents; The preparation method of the anti-ultraviolet additive comprises the following steps: Step 1: Add 2-hydroxy-4-(methacryloyloxy)benzophenone to ethanol and mix well, then add initiator, raise the temperature to 80-90°C, stir for 1-2h, and obtain UV-resistant polymer; Step 2: adding graphene oxide to N,N-dimethylformamide, mixing, ultrasonically dispersing for 10-15 minutes to form a uniform dispersion, then adding glycerol and anti-ultraviolet polymer, stirring at room temperature for 3-5 hours, separating, filtering, washing, and drying to obtain an anti-ultraviolet additive; The initiator is ammonium persulfate; The preparation method of the high temperature resistant additive comprises the following steps: Step A, adding talc powder to toluene, stirring evenly to form a suspension, adding 3-mercaptopropionic acid and a catalyst, heating to 90-100° C., stirring for 1-2 hours, filtering, and drying to obtain modified talc powder; Step B: adding modified talc to tetrahydrofuran, stirring evenly, adding vinyl silicone resin and photoinitiator, reacting under ultraviolet light for 1-2 hours, filtering, and drying to obtain a high temperature resistant additive.
2. The polymer composite material for a warning light housing according to claim 1, characterized in that: In step A, the catalyst is p-toluenesulfonic acid.
3. The polymer composite material for a warning light housing according to claim 1, characterized in that: In step B, the photoinitiator is benzoin dimethyl ether.
4. The polymer composite material for a warning light housing according to claim 1, characterized in that: In step B, the vinyl content of the vinyl silicone resin is 1.4%.
5. The polymer composite material for a warning light housing according to claim 1, characterized in that: The lubricant is one or more of calcium stearate, magnesium stearate, and iron stearate; the plasticizer is tri-n-butyl citrate or dioctyl sebacate; and the crosslinking agent is one of diisopropyl peroxide, benzoyl peroxide, or di-tert-butyl peroxide.
6. A method for preparing a polymer composite material for a warning light housing as claimed in claim 1, characterized in that: The following steps are involved: The first step is to add polyethylene, anti-ultraviolet additives, high temperature resistant additives, lubricants, plasticizers, and cross-linking agents into a mixer for mixing at a speed of 50-80 r / min for 15-30 min to obtain a mixed material; The second step is to add the mixed material into a twin-screw extruder, melt extrude, cool, and pelletize to obtain a polyethylene composite material.
7. The method for preparing a polymer composite material for a warning light housing according to claim 6, characterized in that: In the second step, during the melt extrusion, the temperature is set to 160-220° C. and the twin-screw speed is set to 80-150 r / min.
Citation Information
Patent Citations
Anti-fog, breathable, aging-resistant transparent polyethylene composite material and preparation method thereof
CN115490940B
PE composite material for power pipe and preparation method of PE composite material
CN117603517A